2022
DOI: 10.1371/journal.pgph.0000211
|View full text |Cite
|
Sign up to set email alerts
|

Model-informed target product profiles of long-acting-injectables for use as seasonal malaria prevention

Abstract: Seasonal malaria chemoprevention (SMC) has proven highly efficacious in reducing malaria incidence. However, the continued success of SMC is threatened by the spread of resistance against one of its main preventive ingredients, Sulfadoxine-Pyrimethamine (SP), operational challenges in delivery, and incomplete adherence to the regimens. Via a simulation study with an individual-based model of malaria dynamics, we provide quantitative evidence to assess long-acting injectables (LAIs) as potential alternatives to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…We performed this analysis by replicating protective efficacy outcomes from a randomised non-inferiority trial of dihydroartemisinin-piperaquine (DHA-PPQ) to SP-AQ, 26 following the approach described by Burgert and colleagues. 27 SP-AQ’s protective efficacy against clinical case incidence was extracted from Zongo and colleagues. 26 For each SMC modelling approach (blood stage only, dominant blood stage, and dominant liver stage), we used OpenMalaria to perform in-silico clinical trials for a wide range of model parameter values.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed this analysis by replicating protective efficacy outcomes from a randomised non-inferiority trial of dihydroartemisinin-piperaquine (DHA-PPQ) to SP-AQ, 26 following the approach described by Burgert and colleagues. 27 SP-AQ’s protective efficacy against clinical case incidence was extracted from Zongo and colleagues. 26 For each SMC modelling approach (blood stage only, dominant blood stage, and dominant liver stage), we used OpenMalaria to perform in-silico clinical trials for a wide range of model parameter values.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis then applied a mathematical framework for predicting determinants of intervention impact and defining minimum drug profile criteria. This framework has been previously described, 28 and was demonstrated in a proof-of-concept study 27 (as summarised in appendix 1.4). In brief, we used the individual-based malaria transmission model to simulate scenarios over a wide range of input values for intervention coverage and drug initial efficacy and duration of protection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently very little is known about the PK/PD relationship of monoclonal antibodies. Previous modelling has shown that the protection of an anti-infective malaria monoclonal over time, informed by PK/PD data and models, is an important driver of public health impact 10 . Unlike vaccines, where immune correlates of protection are challenging to define, mAbs offer the potential to provide early PK/PD evidence.…”
Section: Modelling To Support Clinical Trial Translationmentioning
confidence: 99%
“…Modeling has highlighted the importance of the pharmacodynamics of seasonal injectable interventions requiring sustained high levels of protection for the duration or longer of the transmission season to achieve non-inferiority to seasonal malaria chemoprevention. 8 …”
Section: Main Textmentioning
confidence: 99%